3-D periodic CFD model of the heating system in a coke oven battery. Issue 4 (29th April 2014) - Smolka, Jacek; Fic, Adam; J. Nowak, Andrzej; Kosyrczyk, Ludwik
Abstract : Purpose: – The purpose of this paper is to develop a 3-D fully transient numerical model of the heat and fluid flow associated with the chemical reactions that occur in the heating system of the coke oven battery. As a result, the model can be used to provide data for the control system of the battery to reduce energy consumption and emissions and to obtain a product of the desired quality. Design/methodology/approach: – In the proposed model, an accurate representation of the heating flue geometry, the volumetric heat sources as a result of the coke oven gas combustion, the temperature- and mole fraction-dependent properties of the gases were taken into account. The most important part of the model was the unsteady boundary condition definition that allowed the modeling of the periodic heat delivery to the two oven heating walls, both in the coking and the reversion cycles. Findings: – The temperatures obtained using the computational fluid dynamics (CFD) model showed the same pattern of temperature variations as that observed in the experiments. It was also found that the quality of the temperature variation predictions was highly dependent on the radiation model settings. Originality: – The CFD models available in the literature describe the steady or pseudo-steady state operation of the heating system of the coke oven battery. The model developed in this work fully reflects the unsteady character of this heating system. Moreover, the proposed model is prepared for coupling with a model of the coking process that occurs in the two neighboring coke oven chambers.